Effects of huperzine A on secretion of nerve growth factor in cultured rat cortical astrocytes and neurite outgrowth in rat PC12 cells - Tang Li-li; Wang Rui; Tang Xi-can (Acta Pharmacologica Sinica, 2016)
Aim: To study the effects of huperzine A (HupA) on neuritogenic activity and the expression of nerve growth factor (NGF). Methods: After being treated with 10 mumol/L HupA, neurite outgrowth of PC12 cells was observed and counted under phase-contrast microscopy. Mitogenic activity was assayed by [3H]thymidine incorporation. Cell cytotoxicity was evaluated by lactate dehydrogenase (LDH) release. AChE activity, mRNA and protein expression were measured by the Ellman's method, RT-PCR, and Western blot, respectively. NGF mRNA and protein levels were determined by RT-PCR and ELISA assays. Results: Treatment of PC12 cells with 10 mumol/L HupA for 48 h markedly increased the number of neurite-bearing cells, but caused no significant alteration in cell viability or other signs of cytotoxicity. In addition to inhibiting AChE activity, 10 mumol/ L HupA also increased the mRNA and protein levels of this enzyme. In addition, following 2 h exposure of the astrocytes to 10 mumol/L HupA, there was a significant up-regulation of mRNA for NGF and P75 low-affinity NGF receptor. The protein level of NGF was also increased after 24 h treatment with HupA. Conclusion: Our findings demonstrate for the first time that HupA has a direct or indirect neurotrophic activity, which might be beneficial in treatment of neurodegenerative disorders such as Alzheimer disease.